The Role of Nonverbal Communication in Enhancing Interaction in Online Learning Environments - Ainul Yaqin, Mukhamad Ainul Yaqin (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2024)
This study aims to explain nonverbal communication during online learning, nonverbal communication that can support verbal communication. Online learning is indeed not uncommon anymore, performance as a good communication is necessary so that it becomes effective communication in learning at the Informatics Engineering Study Program, University of Yudharta Pasuruan. This study applies Harold Lasswell's Theory (Who Says What In Which Channel to Whom With What Effect). Qualitative descriptive research method and type of research Case study. The subjects studied in this study were lecturers who taught. Data were collected through observation, interviews and documentation. The data that has been collected is analyzed with MDAP, source triangulation analysis, data presentation and conclusions. The research was conducted at the Informatics Engineering study program, Yudharta University, Pasuruan. This research was conducted from January to February 2022. The results of the study stated that the phenomena of nonverbal communication that occurred were facial expressions in the form of a smile, Giving gazes to participants as a form of eye gaze to participants, Hand gestures (movement of describing items, counting movements and greeting movements) which is done when explaining to help participants understand the material from the resource persons, Appearance (virtual background and clothing) to increase interest and increase the focus of participants. All of this has the effect of strengthening learning communication with the effects obtained by participants, including: increasing student enthusiasm for learning, bringing pleasure in lectures, making it easier to understand the material, and appearance as a figure to be imitated